The age of knights and friars, popes and reformers : the history of the Christian church from Leif Eirikson to Martin Luther (AD 1000-1517) - Churchill, Leigh (Milton Keynes, UK : Authentic Media, 2004)
Includes bibliographical references and index.
Keywords: Church history -- 11th century; Church history -- 12th century; Church history -- 13th century; Church history -- 14th century; Church history -- 15th century